2009
DOI: 10.1152/ajpheart.01316.2008
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of cardiac myocyte dysfunction as a unique mechanism of rescue by P2X4 receptors in cardiomyopathy

Abstract: Binary cardiac transgenic (Tg) overexpression of P2X(4) receptors (P2X(4)R) improved the survival of the cardiomyopathic calsequestrin (CSQ) mice. Here we studied the mechanism of rescue using binary P2X(4)R/CSQ Tg and CSQ Tg mice as models. Cellular and intact heart properties were determined by simultaneous sarcomere shortening (SS) and Ca(2+) transients in vitro and echocardiography in vivo. Similar to a delay in death, binary mice exhibited a slowed heart failure progression with a greater left ventricular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…Consistent with improved systolic contractile function, the forward output was also greater in MRS2339-infused than in vehicleinfused CSQ mice. By in vivo heart function measure, the FS was also similarly improved in CSQ animals infused with MRS2339 (current data) and those overexpressing the P2X 4 R (Shen et al, 2009). The present data showed that the HF rescuing effect by either MRS2339 infusion or cardiac overexpression of P2X 4 R was associated with a better preservation of LV wall thickness during systole and diastole in both mouse models.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Consistent with improved systolic contractile function, the forward output was also greater in MRS2339-infused than in vehicleinfused CSQ mice. By in vivo heart function measure, the FS was also similarly improved in CSQ animals infused with MRS2339 (current data) and those overexpressing the P2X 4 R (Shen et al, 2009). The present data showed that the HF rescuing effect by either MRS2339 infusion or cardiac overexpression of P2X 4 R was associated with a better preservation of LV wall thickness during systole and diastole in both mouse models.…”
Section: Discussionsupporting
confidence: 58%
“…Much of the evidence was based on a salutary phenotype in mice with HF with transgenic overexpression of the P2X 4 R (Yang et al, 2004;Sonin et al, 2008;Shen et al, 2009), an important subunit of the endogenous cardiac P2X receptor (Shen et al, 2006). The role of the endogenous cardiac P2X receptor and characterization of its action in improving HF are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14,15 To activate endogenous P2X 4 receptors in mice with heart failure, a hydrolysis-resistant adenine nucleotide (MRS2339) with agonist activity at cardiomyocyte P2X 4 receptors was infused chronically in calsequestrin-overexpressing and postinfarct heart failure mice as well as in dogs with pacing-induced heart failure. MRS2339 infusion at low dosage was able to protect these animals with heart failure, similar to the protective effect exerted by cardiac-specific transgenic overexpression of the P2X 4 receptor.…”
Section: Potential Role Of P2x 4 Receptors In Response To Extracellulmentioning
confidence: 99%